Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantu Alat Praktikum Sederhana Terhadap Hasil Belajar Siswa SMA - Rizky Restu Fauzy; Ratman Ratman (JURNAL BANUA OGE TADULAKO, 2023)
This research was conducted to determine the effect of the class Xa student learning model as an experimental class using the guided inquiry method with the help of simple practical tools. This type of research is experimental research using pretest-posttest control. The sample in this study was 28 in the experimental class and 27 in the control class at SMA Negeri 1 Sausu. Testing the research data using statistical analysis of one-party t-test with prerequisite test with normality test and homogeneity test. The results of the analysis of the data showed that both the experimental class and the control class had data that were normally distributed. Based on the homogeneity test, it can be concluded that there is no difference in variance between the control class and the experimental class, so the data is homogeneous.